Azide Decomposition as a Pathway to Intramolecularly Upper-Rim-Bridged Calix[4]arenes - Tlustý, Martin; Eigner, Václav; Lhoták, Pavel (Synthesis, 2021)
Proximally single-atom-bridged calix[4]arenes possess a rigidified cavity and, thus, unusual complexation properties. Here, we report on the synthesis of the first such heteroatom-bridged compound: amine-bridged calix[4]arene. This compound, prepared by thermal decomposition of 4-azidocalix[4]arene, was obtained alongside very interesting rearranged, inherently chiral 10H-azepino[1,2-a]indole derivatives. NMR titration confirmed the suitability of the amine cavity for the complexation of methylammonium cations; moreover, the –NH– bridge function enables its further derivatization.
Keywords: calixarenes; azide decomposition; bridging; inherent chirality; complexation